Multistaged retrograde intrarenal surgery for large renal stones – our institutional experience - Periasamy Ponnusamy; Rajasekar Sundaram; Rajkumar Ramakrishnan; Sammohit Gulakavarapu; Shravankumar Savadatti (Asian Journal of Medical Sciences, 2023)
Background: Recent advances such as retrograde intrarenal surgery (RIRS) have become an acceptable and widespread technique for upper urinary tract stone management. However, the outcome and complication of staged RIRS for large stone burden (>2.0) still needs to be reported. A total of 150 cases of renal calculi were treated by RIRS in a single center. Among these, 30 had renal stone size larger than 2.0 cm. Aims and Objectives: This study was conducted to present our views, experience, and outcomes of Retrograde Intra Renal Surgery for the Management of Large Renal Stones in Staged Manner using Flexible Ureteroscope with Holmium Laser as energy Source. Materials and Methods: Between March 2020 and January 2022, we admitted 150 patients with upper urinary tract stones who underwent RIRS using 30 Watt Holmium laser lithotripsy in our institute. Post-surgery, all the cases are evaluated in terms of stone free rates (SFR) complications and effectiveness of RIRS. Results: A total of 150 patients having upper urinary tract stones were included in this study (84 male and 66 female patients). All patients underwent RIRS using 30 watt holmium laser lithotripter. The overall SFR was 90.6%. The average stone size was 1.1 cm with average operation time of 100.6 min. Average hospital stay was 2.2 days. The average pain score was 2.1/10 by the Numerical Rating Scale. No major complications (Clavien Dindo III- V) were noted in the study groups. Conclusion: Through our study, we concluded that RIRS for large renal stone management is an effective and safe treatment modality currently.